Reagent Effect: Counterproductive Behavior and Psychological Capital - ASIA ZAMAN; MEHNAZ; DR. SAREER BADSHAH (Journal of Business & Tourism, 2021)
Counter Productive Work Behaviour (CWB) is vibrant phenomena existing in contemporary workplace setting which has to be encountered. This study explores the Psychological Capital (PC) interference towards controlling CWB. Study structure was based on quantitative and cross sectional research. Questionnaires were distributed amid 240 workers of SNGPL KPK, Pakistan. Structure Equation Modeling (SEM) besides regression plus correlation techniques was applied for data analysis. The outcomes of study explore that there occurs solid affirmative correlation amid PC interference in the direction of controlling CWB. The forthcoming research zone is also integrated in this study.